TAHLIL AL-MUHTAWA LI AL-KITAB AL-MADRASI AL-ARABIYAH LI AL-ALAM ALA NADZARIYAH MACKEY تحليل المحتوى للكتاب المدرسي العربية للعالم على نظرية ماجكي: Tahlil Al-Muhtawa Li Al-Kitab Al-Madrasi Al-Arabiyah Li Al-Alam Ala Nadzariyah Mackey - Widiarto, Topo; Nursalam, Yufridal Fitri; Ainurrofiq, Faiq (Arabic Language and Education, 2024)
This study aims to analyze the selection, gradation, presentation, and repetition of materials in the book Al-Arabiyyah Li Al-Alam using Mackey's theory. The background of this research is the use of textbooks from Middle Eastern countries in learning Arabic in Indonesia which is considered difficult for non-Arab beginners. This poses a problem because the language used is too heavy and not necessarily suitable. This research is important because of the low evaluation of Arabic textbooks by the National Education Standards Agency. This study uses a literature method with a descriptive approach. Data were collected through documentation and analyzed using content analysis and tested by theoretical triangulation. The results of the study show that the material in this book is generally in accordance with the standards, program objectives, and student abilities, but it is not clear regarding the suitability with the duration of learning. Gradation is done through structural and semantic groupings, with an emphasis on function. The presentation of the material uses ostensive, pictoral, and contextual procedures, without differential procedures. Material repetition is effective for dialogue, reading, and writing, but listening skills are not accommodated in this book.